The effect of bio ethical principles education on ethical attitude of prehospital paramedic personnel - Mohammad Mahdi Doust Mohammadi; Hakimeh Sheikhasadi; Shahla Ayoubi Mahani; Abolfazl Taheri; Hojjat Sheikhbardsiri; Kamel Abdi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Ethical attitude of paramedic personnel is one of the most important factors in their effective and useful performance. Therefore, according to the importance of this issue and immense effect of religious culture on the formation of ethics, this study aimed to effect bio-ethical principles teaching on moral attitude of paramedic emergency personnel in Iran. Material and Methods: The present study was an experimental study carried out in 2020 on 60 of paramedic emergency personnel. Samples were available, randomly selected and assigned to two groups of control and intervention. The intervention was performed for a 2-h workshop of bioethical principles in 4 day based on Quran verses. Moral attitude of both groups was studied before and after each intervention. Data were analyzed using Kolmogorov-Simonov, Chi-square, t-test, one-way, and paired t-test with SPSS version 16 (P ≤ 0/05). RESULTS: Ethical attitude means for both groups of control and intervention demonstrated that ethical attitude has meaningfully increased after the workshop. Demographic variables such as age, gender, and work experience of participants in workshops were not different between these two groups (P < 0/05). The study of these two groups showed that there is no relationship among work experience, gender, marital status, age, and ethical attitude. CONCLUSION: Prehospital emergency is quite different from the other occupations in health-care system and the ethical issues of this field are more important. Therefore, teaching in workplace and through ethical principles based on religious teachings will have a profound effect on improving biological ethics of paramedic prehospital staffs.